2008
DOI: 10.1007/s00540-008-0665-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual hallucinations on eye closure after orthopedic surgery under general anesthesia

Abstract: A 61-year-old woman suffering from rheumatoid arthritis without a contributory neurological, mental, or psychological history experienced visual hallucinations solely on eye closure after total hip arthroplasty under general anesthesia combined with epidural anesthesia. The visual hallucinations first appeared when she arose from sleep early on postoperative day 1, approximately 12 h after the end of surgery. Only on closing her eyes, she had a clear view of colored clothes, lace curtains, handbags, hats, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Closed-eye visual hallucinations have previously been reported following general anesthesia, local anesthesia with lidocaine, and atropine poisoning. [15][16][17][18][19] While hallucinations are not strictly a sensory misperception, these closed-eye visual hallucinations may be considered an AIWS symptom in view of its link to the patient's VM attacks, and because hallucinations (e.g., zoopsia) have been considered manifestations of AIWS in previous publications. 3,8 An unusual finding in our cohort is the high proportion (41%) with extrapersonal misperceptions (4 with out-ofbody experiences, 2 with derealization, 1 with depersonalization) compared to other migraine-related AIWS studies.…”
Section: Discussionmentioning
confidence: 99%
“…Closed-eye visual hallucinations have previously been reported following general anesthesia, local anesthesia with lidocaine, and atropine poisoning. [15][16][17][18][19] While hallucinations are not strictly a sensory misperception, these closed-eye visual hallucinations may be considered an AIWS symptom in view of its link to the patient's VM attacks, and because hallucinations (e.g., zoopsia) have been considered manifestations of AIWS in previous publications. 3,8 An unusual finding in our cohort is the high proportion (41%) with extrapersonal misperceptions (4 with out-ofbody experiences, 2 with derealization, 1 with depersonalization) compared to other migraine-related AIWS studies.…”
Section: Discussionmentioning
confidence: 99%
“…A unifying feature of these hallucinations is that they occur when the patient's eyes are open. A review of the literature shows that cases of closed-eye hallucinations have been reported in postoperative patients who received general anesthesia or rarely in temporal lobe epilepsy [ 3 ]. The patient in this case had not received any drugs known to be hallucinogenic and did not have history of seizures or any evidence of seizure during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Previous cases of visual hallucinations occurring on eye closure have been reported following hip surgery under general anaesthesia [1], local anaesthesia with lidocaine [2,3], atropine administration [4], cardiovascular surgery [5,6], traumatic subdural hematoma in the left occipital region [7], trans-sphenoidal adenomectomy [8] and posterior callosal stroke [9]. The triggering of hallucinations by eye closure can be linked to the "cortical release phenomenon" due to visual Visual Hallucinations with Disembodiment and Self-Motion Illusion on Eye Closure after Brain Cyst Drainage: A Case Report deafferentation in Charles-Bonnet Syndrome [7].…”
Section: Discussionmentioning
confidence: 99%
“…We report the first documented case of visual hallucinations associated with disembodiment and self-motion illusion, observed after brain cyst drainage. Visual hallucinations on eye closure have been previously reported [1][2][3][4][5][6][7][8][9], but never with disembodiment nor self-motion illusion.…”
Section: Case Reportmentioning
confidence: 99%